Phenylpropanoids isolated from Piper sarmentosum Roxb. induce apoptosis in breast cancer cells through reactive oxygen species and mitochondrial-dependent pathways. (5th January 2018) - Hematpoor, Arshia; Paydar, Mohammadjavad; Liew, Sook Yee; Sivasothy, Yasodha; Mohebali, Nooshin; Looi, Chung Yeng; Wong, Won Fen; Azirun, Mohd Sofian; Awang, Khalijah
Abstract: The aim of the present study is to isolate bioactive compounds from the roots of Piper sarmentosum and examine the mechanism of action using human breast cancer cell line (MDA-MB-231). Bioassay guided-fractionation of methanolic extract led to the isolation of asaricin (1 ) and isoasarone (2 ). Asaricin (1 ) and isoasarone (2 ) had significant cytotoxicity towards MDA-MB-231. MCF-10A (human normal breast epithelial cells) cells are less sensitive than MDA-MB-231, but they respond to the treatment with the same unit of measurement. Both compounds increase reactive oxygen species (ROS), decrease mitochondrial membrane potential (MMP) and enhance cytochrome c release in treated MDA-MB-231 cells. Isoasarone (2 ) markedly elevated caspase -8 and -3/7 activities and caused a decline in nuclear NF-κB translocation, suggesting extrinsic, death receptor-linked apoptosis pathway. Quantitative PCR results of MDA-MB-231 treated with asaricin (1 ) and isoasarone (2 ) showed altered expression of Bcl-2: Bax level. The inhibitory potency of these isolates may support the therapeutic uses of these compounds in breast cancer. Highlights: Asaricin and isoasarone were isolated from the methanol extract of roots of Piper sarmentosum. Asaricin and isoasarone significantly inhibited growth of human breast cancer MDA-MB-231. Asaricin induced apoptosis through intrinsic mitochondrial pathway. Isoasarone activates extrinsic death receptor pathway in MDA-MB-231. Both compounds altered ratio of Bcl-2: Bax expression in MDA-MB-231.